PERSEPSI MAHASISWA TERHADAP PENGGUNAAN LAGU BAHASA INGGRIS UNTUK PEMBELAJARAN BAHASA INGGRIS - LOLONG, SAUN; MARENTEK, ANDRIYANI; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research is entitled ?Students? Perception on the Use of English Songs for Learning English?. The objectives of the research are to identify, classify, and describe the students? perception about learning English using song. Also, it is to analyze and describe the aspects of learning that can increase students? English skills through listening English song. This research used descriptive method. The writer collected data by interviewing 20 participants at English Department, Faculty of Humanities, Sam Ratulangi University. The writer has found seven perceptions as the result of this research They are The Use of English songs to learning English is fun; not boring; effective learning media; entertaining; media to learn about culture; encouragement to learn; improve brain capacity. In this research, the writer also found improvement in students? vocabulary, pronounciation, listening and speaking skills. There are 15 students feel the improvement in their vocabulary skill, 16 students in pronounciation skill, 15 students in listening skill and 17 students in speaking skill. Keywords: Students? perception, English Learning, Learning media, Song